A preparation process of honeycomb activated carbon for air purification
By preparing honeycomb activated carbon with a composite network structure and high pores, the problem of low indoor VOCs purification efficiency in existing technologies has been solved, and high -efficiency and safe air purification effects are achieved.
Patent Information
- Application Number
- CN202411356517.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The prior art has high operating costs, insufficient safety guarantee and low purification efficiency when processing indoor volatile organic compounds (VOCs). Adsorption method, as the most promising method, still needs to be improved to improve adsorption performance.
By preparing a honeycomb activated carbon for air purification, the crafts include the pre -treatment of bamboo dandruff powder, the polymer mixed fluid impregnation, carbonization, hydrogen peroxide solution oxidation and silicate ball grinding, forming a composite network structure and high pores activated carbon Essence
Improve the adsorption performance of activated carbon, ensure the stability and air purification effect of the pores, and enhance the adsorption ability to indoor VOCs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon and relates to a preparation process of honeycomb activated carbon for air purification. Background Art
[0002] Indoor volatile organic compounds (VOCs) are an important cause of the decline in indoor air quality. There are many types of VOCs, which can be divided into alkanes, aromatic hydrocarbons, alkenes, esters, aldehydes, etc. according to their structure. They mainly come from decoration materials and various furniture, human activities and outdoor sources. VOCs are toxic, volatile and carcinogenic.
[0003] At present, VOCs purification methods including thermal catalytic oxidation, photocatalytic oxidation, plasma catalytic method and biofiltration have been widely used in the treatment of industrial waste gas. However, they are rarely used in the treatment of indoor VOCs due to their high operating costs, lack of safety guarantee and low purification efficiency. Adsorption is considered to be the most promising indoor VOCs treatment method because of its convenient operation, low cost, high efficiency and no by-products. Adsorbent is an important factor in determining the degree of air purification treatment. Porous media are often made into adsorbents because of their large specific surface area. At present, the widely used porous adsorption materials include activated carbon, molecular sieves, activated alumina, etc.
[0004] Activated carbon is made from some carbon-rich materials such as coal, wood, and fruit shells through carbonization, activation and other production processes. Activated carbon is divided into macropores, mesopores and micropores. Macropores are diffusion channels for adsorbate molecules, mesopores can adsorb larger adsorbate molecules, and capillary condensation will occur under higher relative pressures. Micropores are the main adsorption sites, and their high content determines the saturated adsorption capacity of activated carbon. Therefore, increasing the number of micropores is one of the important means to improve the adsorption performance of activated carbon. Summary of the invention
[0005] The present invention relates to a preparation process of honeycomb activated carbon for air purification, and belongs to the field of activated carbon technology. The present invention discloses a preparation process of honeycomb activated carbon for air purification, which is as follows: (1) bamboo chips are sieved and then heated, and sieved twice to obtain bamboo chip powder; (2) bamboo chip powder is stirred and mixed with phosphoric acid solution, and then activated, and taken out and cooled to room temperature to form pre-treated bamboo chip powder; (3) pre-treated bamboo chip powder is immersed in polymer mixed solution, and then dried at low temperature, moved to a baking oven for carbonization, and taken out and cooled to room temperature to obtain solidified activated carbon; (4) solidified activated carbon is mixed with hydrogen peroxide solution and placed, and then dried in a vacuum drying oven, and then cooled to obtain modified activated carbon; (5) modified activated carbon is mixed with silicate, ball milled, mud pressed, extruded, and dried to obtain honeycomb activated carbon for air purification. The pores of the honeycomb activated carbon prepared by the present invention will not collapse, and the air purification effect is excellent.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A preparation process of honeycomb activated carbon for air purification, the preparation process of honeycomb activated carbon for air purification is as follows:
[0008] (1) After the bamboo chips are sieved, they are heated and dried, and sieved for the second time to obtain bamboo chip powder;
[0009] (2) mixing the bamboo dust powder with the phosphoric acid solution, activating the mixture, and cooling the mixture to room temperature to form pretreated bamboo dust powder;
[0010] (3) soaking the pretreated bamboo powder in a polymer mixture, then drying at low temperature, moving it to a baking oven for carbonization, and taking it out and cooling it to room temperature to obtain solidified activated carbon;
[0011] (4) mixing the solidified activated carbon with the hydrogen peroxide solution and placing the mixture, then drying the mixture in a vacuum drying oven, and cooling the mixture to obtain the modified activated carbon;
[0012] (5) The modified activated carbon is mixed with silicate, ball-milled, squeezed, and formed by extrusion through a mold. After drying, honeycomb activated carbon for air purification can be obtained.
[0013] Furthermore, the mesh sizes of the first sieving and the second sieving in step (1) are 10-30 mesh and 100-300 mesh respectively, and the temperature and time of the heating are 60-80° C. and 30-60 min respectively.
[0014] Furthermore, in the step (2), the solid-liquid ratio of bamboo dust powder to phosphoric acid solution is 1-5:8-10 g / mL, wherein the mass fraction of phosphoric acid solution is 38-45%, the mixing time is 15-25 min, and the activation temperature and time are 200-300° C. and 15-20 min, respectively.
[0015] Furthermore, in the step (3), the solid-liquid ratio of the pretreated bamboo dust powder to the polymer mixture is 1-3:10-15 g / mL, wherein the polymer mixture is composed of polyacrylate, polyamide and acetone in a mass ratio of 1:1.5:10-20, the immersion time is 1-2 h, the temperature and time of the low-temperature drying are 40-50 ° C and 1-2 h respectively, and the temperature and time of the carbonization are 150-250 ° C and 40-60 min respectively.
[0016] Furthermore, in the step (4), the solid-liquid ratio of the solidified activated carbon to the hydrogen peroxide solution is 1:25 g / mL, wherein the mass fraction of the hydrogen peroxide solution is 20-30%, the placement time is 12-24 h, and the temperature and time of the vacuum drying are 80-100° C. and 3 h, respectively.
[0017] Furthermore, in the step (5), the mass ratio of the modified activated carbon to the silicate is 10:0.5-1, wherein the silicate is composed of diatomaceous earth, clay and perlite in a mass ratio of 1:1:1.
[0018] Furthermore, the ball milling in step (5) is specifically as follows: the modified activated carbon and silicate are added with distilled water and ground in a ball mill for 20-26 hours to form a slurry, wherein the volume of the distilled water accounts for 60-75% of the volume of the slurry, and the mud pressing refers to placing the slurry into a mud press for filter pressing.
[0019] Furthermore, in step (5), the drying temperature and time are 80-100° C. and 12-24 h, respectively.
[0020] Beneficial effects of the present invention:
[0021] 1. The present invention first pre-treats bamboo dust with phosphoric acid to remove ash in the pores of activated carbon and prevents clogging of the pores; at the same time, a composite network structure is formed on the outer surface of the activated carbon pores through polyacrylate and polyamide, and the pores will not be blocked; finally, a hydrogen peroxide solution is used to oxidize the activated carbon to reduce the polarity of the activated carbon, enhance its non-polarity, and further enhance the adsorption of indoor volatile organic compounds. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.
[0023] Example 1
[0024] A preparation process of honeycomb activated carbon for air purification, the preparation process of honeycomb activated carbon for air purification is as follows:
[0025] (1) After the bamboo chips are sieved, they are heated and dried, and sieved for the second time to obtain bamboo chip powder;
[0026] (2) mixing the bamboo dust powder with the phosphoric acid solution, activating the mixture, and cooling the mixture to room temperature to form pretreated bamboo dust powder;
[0027] (3) soaking the pretreated bamboo powder in a polymer mixture, then drying at low temperature, moving it to a baking oven for carbonization, and taking it out and cooling it to room temperature to obtain solidified activated carbon;
[0028] (4) mixing the solidified activated carbon with the hydrogen peroxide solution and placing the mixture, then drying the mixture in a vacuum drying oven, and cooling the mixture to obtain the modified activated carbon;
[0029] (5) The modified activated carbon is mixed with silicate, ball-milled, squeezed, and formed by extrusion through a mold. After drying, honeycomb activated carbon for air purification can be obtained.
[0030] The mesh sizes of the first sieving and the second sieving in the step (1) are 10 mesh and 100 mesh respectively, and the temperature and time of the heating are 60° C. and 30 minutes respectively.
[0031] In the step (2), the solid-liquid ratio of bamboo dust powder to phosphoric acid solution is 1:8 g / mL, wherein the mass fraction of phosphoric acid solution is 38%, the mixing time is 15 min, and the activation temperature and time are 200° C. and 15 min, respectively.
[0032] In the step (3), the solid-liquid ratio of the pretreated bamboo dust powder to the polymer mixture is 1:10 g / mL, wherein the polymer mixture consists of polyacrylate, polyamide and acetone in a mass ratio of 1:1.5:10, the immersion time is 1 hour, the temperature and time of the low-temperature drying are 40°C and 1 hour respectively, and the temperature and time of the carbonization are 150°C and 40 minutes respectively.
[0033] In the step (4), the solid-liquid ratio of the solidified activated carbon to the hydrogen peroxide solution is 1:25 g / mL, wherein the mass fraction of the hydrogen peroxide solution is 20%, the standing time is 12 h, and the temperature and time of the vacuum drying are 80° C. and 3 h, respectively.
[0034] In the step (5), the mass ratio of modified activated carbon to silicate is 10:0.5, wherein the silicate is composed of diatomaceous earth, clay and perlite in a mass ratio of 1:1:1.
[0035] The ball milling in step (5) is specifically as follows: adding distilled water to the modified activated carbon and silicate and grinding them in a ball mill for 20 hours to form a slurry, wherein the volume of the distilled water accounts for 60% of the volume of the slurry, and the mud pressing refers to placing the slurry into a mud press for filter pressing.
[0036] The drying temperature and time in step (5) are 80° C. and 12 h, respectively.
[0037] The purchasing source of the polyacrylate: polyacrylate / Jinan Feiyue Chemical Co., Ltd., the purchasing source of polyamide: polyamide / PA9T Japan Kuraray-GN2330, the purchasing source of diatomaceous earth: diatomaceous earth / Lingshou County Jiaao Mineral Products Co., Ltd., the purchasing source of clay: clay / Foshan Dongyu Ceramics Equipment Co., Ltd., the purchasing source of perlite: perlite / Puyang Changshun Insulation Technology Co., Ltd.
[0038] Example 2
[0039] A preparation process of honeycomb activated carbon for air purification, the preparation process of honeycomb activated carbon for air purification is as follows:
[0040] (1) After the bamboo chips are sieved, they are heated and dried, and sieved for the second time to obtain bamboo chip powder;
[0041] (2) mixing the bamboo dust powder with the phosphoric acid solution, activating the mixture, and cooling the mixture to room temperature to form pretreated bamboo dust powder;
[0042] (3) soaking the pretreated bamboo powder in a polymer mixture, then drying at low temperature, moving it to a baking oven for carbonization, and taking it out and cooling it to room temperature to obtain solidified activated carbon;
[0043] (4) mixing the solidified activated carbon with the hydrogen peroxide solution and placing the mixture, then drying the mixture in a vacuum drying oven, and cooling the mixture to obtain the modified activated carbon;
[0044] (5) The modified activated carbon is mixed with silicate, ball-milled, squeezed, and formed by extrusion through a mold. After drying, honeycomb activated carbon for air purification can be obtained.
[0045] The mesh sizes of the first sieving and the second sieving in the step (1) are 20 mesh and 200 mesh respectively, and the temperature and time of the heating are 70° C. and 45 minutes respectively.
[0046] In the step (2), the solid-liquid ratio of bamboo dust powder to phosphoric acid solution is 3:9 g / mL, wherein the mass fraction of phosphoric acid solution is 41%, the mixing time is 20 min, and the activation temperature and time are 250° C. and 18 min, respectively.
[0047] In the step (3), the solid-liquid ratio of the pretreated bamboo dust powder to the polymer mixture is 2:12 g / mL, wherein the polymer mixture is composed of polyacrylate, polyamide and acetone in a mass ratio of 1:1.5:15, the immersion time is 1.5 hours, the temperature and time of the low-temperature drying are 45°C and 1.5 hours respectively, and the temperature and time of the carbonization are 200°C and 50 minutes respectively.
[0048] In the step (4), the solid-liquid ratio of the solidified activated carbon to the hydrogen peroxide solution is 1:25 g / mL, wherein the mass fraction of the hydrogen peroxide solution is 25%, the standing time is 18 h, and the temperature and time of the vacuum drying are 90° C. and 3 h, respectively.
[0049] In the step (5), the mass ratio of modified activated carbon to silicate is 10:0.8, wherein the silicate is composed of diatomaceous earth, clay and perlite in a mass ratio of 1:1:1.
[0050] The ball milling in step (5) is specifically as follows: adding distilled water to the modified activated carbon and silicate and grinding them in a ball mill for 23 hours to form a slurry, wherein the volume of the distilled water accounts for 68% of the volume of the slurry, and the mud pressing refers to placing the slurry into a mud press for filter pressing.
[0051] The drying temperature and time in step (5) are 90° C. and 18 h, respectively.
[0052] The purchasing source of the polyacrylate: polyacrylate / Jinan Feiyue Chemical Co., Ltd., the purchasing source of polyamide: polyamide / PA9T Japan Kuraray-GN2330, the purchasing source of diatomaceous earth: diatomaceous earth / Lingshou County Jiaao Mineral Products Co., Ltd., the purchasing source of clay: clay / Foshan Dongyu Ceramics Equipment Co., Ltd., the purchasing source of perlite: perlite / Puyang Changshun Insulation Technology Co., Ltd.
[0053] Example 3
[0054] A preparation process of honeycomb activated carbon for air purification, the preparation process of honeycomb activated carbon for air purification is as follows:
[0055] (1) After the bamboo chips are sieved, they are heated and dried, and sieved for the second time to obtain bamboo chip powder;
[0056] (2) mixing the bamboo dust powder with the phosphoric acid solution, activating the mixture, and cooling the mixture to room temperature to form pretreated bamboo dust powder;
[0057] (3) soaking the pretreated bamboo powder in a polymer mixture, then drying at low temperature, moving it to a baking oven for carbonization, and taking it out and cooling it to room temperature to obtain solidified activated carbon;
[0058] (4) mixing the solidified activated carbon with the hydrogen peroxide solution and placing the mixture, then drying the mixture in a vacuum drying oven, and cooling the mixture to obtain the modified activated carbon;
[0059] (5) The modified activated carbon is mixed with silicate, ball-milled, squeezed, and formed by extrusion through a mold. After drying, honeycomb activated carbon for air purification can be obtained.
[0060] The mesh sizes of the first sieving and the second sieving in the step (1) are 30 mesh and 300 mesh respectively, and the temperature and time of the heating are 80° C. and 60 min respectively.
[0061] In the step (2), the solid-liquid ratio of bamboo dust powder to phosphoric acid solution is 5:10 g / mL, wherein the mass fraction of phosphoric acid solution is 45%, the mixing time is 25 min, and the activation temperature and time are 300° C. and 20 min, respectively.
[0062] In the step (3), the solid-liquid ratio of the pretreated bamboo dust powder to the polymer mixture is 3:15 g / mL, wherein the polymer mixture consists of polyacrylate, polyamide and acetone in a mass ratio of 1:1.5:20, the immersion time is 2 hours, the temperature and time of the low-temperature drying are 50°C and 2 hours respectively, and the temperature and time of the carbonization are 250°C and 60 minutes respectively.
[0063] In the step (4), the solid-liquid ratio of the solidified activated carbon to the hydrogen peroxide solution is 1:25 g / mL, wherein the mass fraction of the hydrogen peroxide solution is 30%, the placement time is 24 hours, and the temperature and time of the vacuum drying are 100° C. and 3 hours, respectively.
[0064] In the step (5), the mass ratio of modified activated carbon to silicate is 10:1, wherein the silicate is composed of diatomaceous earth, clay and perlite in a mass ratio of 1:1:1.
[0065] The ball milling in step (5) is specifically as follows: adding distilled water to the modified activated carbon and silicate and grinding them in a ball mill for 26 hours to form a slurry, wherein the volume of the distilled water accounts for 75% of the volume of the slurry, and the mud pressing refers to placing the slurry into a mud press for filter pressing.
[0066] The drying temperature and time in step (5) are 100° C. and 24 h, respectively.
[0067] The purchasing source of the polyacrylate: polyacrylate / Jinan Feiyue Chemical Co., Ltd., the purchasing source of polyamide: polyamide / PA9T Japan Kuraray-GN2330, the purchasing source of diatomaceous earth: diatomaceous earth / Lingshou County Jiaao Mineral Products Co., Ltd., the purchasing source of clay: clay / Foshan Dongyu Ceramics Equipment Co., Ltd., the purchasing source of perlite: perlite / Puyang Changshun Insulation Technology Co., Ltd.
[0068] Comparative Example 1
[0069] On the basis of Example 2, a preparation process of honeycomb activated carbon for air purification is provided, and the preparation process of honeycomb activated carbon for air purification is specifically as follows:
[0070] (1) After the bamboo chips are sieved, they are heated and dried, and sieved for the second time to obtain bamboo chip powder;
[0071] (2) mixing the bamboo dust powder with the phosphoric acid solution, activating the mixture, and cooling the mixture to room temperature to form pretreated bamboo dust powder;
[0072] (3) pre-treated bamboo dust powder is mixed with hydrogen peroxide solution and placed, then dried in a vacuum drying oven, and cooled to obtain modified activated carbon;
[0073] (4) The modified activated carbon is mixed with silicate, ball-milled, squeezed, and formed by extrusion through a mold. After drying, honeycomb activated carbon for air purification can be obtained.
[0074] The mesh sizes of the first sieving and the second sieving in the step (1) are 20 mesh and 200 mesh respectively, and the temperature and time of the heating are 70° C. and 45 minutes respectively.
[0075] In the step (2), the solid-liquid ratio of bamboo dust powder to phosphoric acid solution is 3:9 g / mL, wherein the mass fraction of phosphoric acid solution is 41%, the mixing time is 20 min, and the activation temperature and time are 250° C. and 18 min, respectively.
[0076] In the step (3), the solid-liquid ratio of the pretreated bamboo dust powder to the hydrogen peroxide solution is 1:25 g / mL, wherein the mass fraction of the hydrogen peroxide solution is 25%, the placement time is 18 hours, and the temperature and time of the vacuum drying are 90° C. and 3 hours, respectively.
[0077] In the step (4), the mass ratio of modified activated carbon to silicate is 10:0.8, wherein the silicate is composed of diatomaceous earth, clay and perlite in a mass ratio of 1:1:1.
[0078] The ball milling in step (4) is specifically as follows: adding distilled water to the modified activated carbon and silicate and grinding them in a ball mill for 23 hours to form a slurry, wherein the volume of the distilled water accounts for 68% of the volume of the slurry, and the mud pressing refers to placing the slurry into a mud press for filter pressing.
[0079] The drying temperature and time in step (4) are 90° C. and 18 h, respectively.
[0080] The diatomaceous earth was purchased from: diatomaceous earth / Lingshou County Jiaao Mineral Products Co., Ltd., the clay was purchased from: clay / Foshan Dongyu Ceramics Equipment Co., Ltd., and the perlite was purchased from: perlite / Puyang Changshun Insulation Technology Co., Ltd.
[0081] Comparative Example 2
[0082] On the basis of Example 2, the polyacrylate in the polymer mixture was removed and replaced with polyamide of equal mass, and other conditions were consistent with Example 2.
[0083] Comparative Example 3
[0084] On the basis of Example 2, the polyamide in the polymer mixture was removed and replaced with an equal mass of polyacrylate, and other conditions were consistent with Example 2.
[0085] Comparative Example 4
[0086] On the basis of Example 2, a preparation process of honeycomb activated carbon for air purification is provided, and the preparation process of honeycomb activated carbon for air purification is specifically as follows:
[0087] (1) After the bamboo chips are sieved, they are heated and dried, and sieved for the second time to obtain bamboo chip powder;
[0088] (2) mixing the bamboo dust powder with the phosphoric acid solution, activating the mixture, and cooling the mixture to room temperature to form pretreated bamboo dust powder;
[0089] (3) soaking the pretreated bamboo powder in a polymer mixture, then drying at low temperature, moving it to a baking oven for carbonization, and taking it out and cooling it to room temperature to obtain solidified activated carbon;
[0090] (4) The solidified activated carbon is mixed with silicate, ball-milled, squeezed, and formed by extrusion through a mold. After drying, honeycomb activated carbon for air purification can be obtained.
[0091] The mesh sizes of the first sieving and the second sieving in the step (1) are 20 mesh and 200 mesh respectively, and the temperature and time of the heating are 70° C. and 45 minutes respectively.
[0092] In the step (2), the solid-liquid ratio of bamboo dust powder to phosphoric acid solution is 3:9 g / mL, wherein the mass fraction of phosphoric acid solution is 41%, the mixing time is 20 min, and the activation temperature and time are 250° C. and 18 min, respectively.
[0093] In the step (3), the solid-liquid ratio of the pretreated bamboo dust powder to the polymer mixture is 2:12 g / mL, wherein the polymer mixture is composed of polyacrylate, polyamide and acetone in a mass ratio of 1:1.5:15, the immersion time is 1.5 hours, the temperature and time of the low-temperature drying are 45°C and 1.5 hours respectively, and the temperature and time of the carbonization are 200°C and 50 minutes respectively.
[0094] In the step (4), the mass ratio of the solidified activated carbon to the silicate is 10:0.8, wherein the silicate is composed of diatomaceous earth, clay and perlite in a mass ratio of 1:1:1.
[0095] The ball milling in step (4) is specifically as follows: adding distilled water to the solidified activated carbon and silicate and grinding them in a ball mill for 23 hours to form a slurry, wherein the volume of the distilled water accounts for 68% of the volume of the slurry, and the mud pressing refers to placing the slurry into a mud press for filter pressing.
[0096] The drying temperature and time in step (4) are 90° C. and 18 h, respectively.
[0097] The purchasing source of the polyacrylate: polyacrylate / Jinan Feiyue Chemical Co., Ltd., the purchasing source of polyamide: polyamide / PA9T Japan Kuraray-GN2330, the purchasing source of diatomaceous earth: diatomaceous earth / Lingshou County Jiaao Mineral Products Co., Ltd., the purchasing source of clay: clay / Foshan Dongyu Ceramics Equipment Co., Ltd., the purchasing source of perlite: perlite / Puyang Changshun Insulation Technology Co., Ltd.
[0098] Performance Testing
[0099] 1. The honeycomb activated carbon prepared in Examples 1-3 and Comparative Examples 1-4 was tested for formaldehyde adsorption rate and antibacterial rate according to the air quality standard GB / T18883-2002.
[0100] The above test results are shown in Table 1.
[0101] Table 1 Test results
[0102]
[0103] From the data analysis in Table 1, it can be concluded that the adsorption rate of formaldehyde in Examples 1-3 is greater than that in Comparative Examples 1-4, and the adsorption values are all above 94%. The antibacterial properties of Examples 1-3 and Comparative Examples 2-4 are all Grade I, while the antibacterial property of Comparative Example 1 is Grade II. In Comparative Example 1, no polymer mixed liquid is added for curing, and the pore structure of the activated carbon is easily collapsed after acid treatment, so the adsorption rate and antibacterial effect are greatly reduced; in Comparative Examples 2-3, a single polymer is added, which cannot form a composite network structure, and the firmness of the pore structure is weaker than that of the embodiment, and thus the adsorption rate and antibacterial effect are also worse than those of the embodiment; in Comparative Example 4, no oxidation treatment with hydrogen peroxide solution is performed, and its polarity is not weakened, and the adsorption of indoor volatile organic compounds is worse than that of the embodiment.
[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A preparation process of honeycomb activated carbon for air purification, characterized in that: The preparation process of the honeycomb activated carbon for air purification is as follows: (1) After the bamboo chips are sieved, they are heated and dried, and sieved for the second time to obtain bamboo chip powder; (2) mixing the bamboo dust powder with the phosphoric acid solution, activating the mixture, and cooling the mixture to room temperature to form pretreated bamboo dust powder; (3) soaking the pretreated bamboo powder in a polymer mixture, then drying at low temperature, moving it to a baking oven for carbonization, and taking it out and cooling it to room temperature to obtain solidified activated carbon; (4) mixing the solidified activated carbon with the hydrogen peroxide solution and placing the mixture, then drying the mixture in a vacuum drying oven, and cooling the mixture to obtain the modified activated carbon; (5) The modified activated carbon and silicate are mixed and ball-milled, the mud is squeezed, and the mixture is extruded through a mold. After drying, honeycomb activated carbon for air purification can be obtained; The mesh sizes of the first sieving and the second sieving in step (1) are 10-30 mesh and 100-300 mesh respectively, and the temperature and time of the heating are 60-80° C. and 30-60 min respectively; In the step (3), the solid-liquid ratio of the pretreated bamboo dust powder to the polymer mixture is 1-3:10-15 g / mL, wherein the polymer mixture is composed of polyacrylate, polyamide and acetone in a mass ratio of 1:1.5:10-20, the immersion time is 1-2 h, the temperature and time of the low-temperature drying are 40-50° C. and 1-2 h, respectively, and the temperature and time of the carbonization are 150-250° C. and 40-60 min, respectively; In the step (5), the mass ratio of modified activated carbon to silicate is 10:0.5-1, wherein the silicate is composed of diatomaceous earth, clay and perlite in a mass ratio of 1:1:
1.
2. The preparation process of honeycomb activated carbon for air purification according to claim 1, characterized in that: In the step (2), the solid-liquid ratio of bamboo dust powder to phosphoric acid solution is 1-5:8-10 g / mL, wherein the mass fraction of phosphoric acid solution is 38-45%, the mixing time is 15-25 min, and the activation temperature and time are 200-300° C. and 15-20 min, respectively.
3. The preparation process of honeycomb activated carbon for air purification according to claim 1, characterized in that: In the step (4), the solid-liquid ratio of the solidified activated carbon to the hydrogen peroxide solution is 1:25 g / mL, wherein the mass fraction of the hydrogen peroxide solution is 20-30%, the placement time is 12-24 h, and the temperature and time of the vacuum drying are 80-100° C. and 3 h, respectively.
4. The preparation process of honeycomb activated carbon for air purification according to claim 1, characterized in that: The ball milling in step (5) is specifically as follows: adding distilled water to the modified activated carbon and silicate and grinding them in a ball mill for 20-26 hours to form a slurry, wherein the volume of the distilled water accounts for 60-75% of the volume of the slurry, and the mud pressing refers to placing the slurry into a mud press for filter pressing.
5. The preparation process of honeycomb activated carbon for air purification according to claim 1, characterized in that: The drying temperature and time in step (5) are 80-100° C. and 12-24 h, respectively.
Citation Information
Patent Citations
Bamboo-based activated carbon with high specific surface area
CN117023580A
Air purification antibacterial activated carbon and preparation method thereof
CN118384855A